Probiotic and Relation to Major Depressive Disorder (MDD) - Rattanakarun, Rachaya (Thai Journal of Toxicology, 2021)
Major depressive disorder (MDD) is a psychiatric disorder that leads to severe mental problem and may cause suicide. Factors that lead to depression consist of genetic factors and environmental factors such as age, stress, diet intake and sedentary lifestyle. Recent findings revealed that gut microbiome dysbiosis has an effect on MDD patients via a communication of gut microbiome, hormone, nervous system and immune system that leads to behavioral, emotional and neurotransmitter change. Probiotics are defined as living bacteria, when administered in adequate amounts, confer a health benefit on the host. Probiotics were used to adjunct therapy in MDD patients to balance gut microbiome composition and reduce side effects from antidepressant drugs. Studies in animal, healthy volunteer and psychiatric patients indicate that consumption of probiotics has mental benefits that reduce stress, negative emotion, anxiety state and depression. Many foods in Thailand have probiotic characteristics but there have been limited studies about the effect of probiotic on psychological outcomes. This review may support the benefits of probiotics in MDD patients and inspire researchers to do the study about the effect of Thai probiotic foods on emotion or psychological outcomes.